Microstructure and mechanical properties of oxide dispersion strengthened high-entropy alloys CoCrFeMnNi and CrFe₂MnNi - Kolodiy, I.V.; Velikodnyi, O.M.; Tikhonovsky, M.A. (Вопросы атомной науки и техники, 2021)
High-entropy alloys (HEAs) CoCrFeMnNi and CrFe₂MnNi, dispersion-strengthened by pre-synthesized nanooxides composition of 80%Y₂O₃+20%ZrO₂ (mol.%) were obtained by mechanical alloying followed by compaction and sintering. Average grain size of the oxide dispersion-strengthened (ODS) alloys was about 2 μm. Oxide precipitates in alloys are characterized by the presence of small particles with an average size of about 10 nm and a density of ≈ 10²¹ m⁻³, as well as small amount of larger particles sizes of 50…150 nm. The qualitative composition of particles of different sizes has been established. Mechanical properties of HEAs were studied at different temperatures. It is shown that strengthening of the studied alloys by nanooxide particles leads to a significant increase in strength characteristics. Методом механічного легування з наступним компактуванням та спіканням отримано високоентропійні сплави CoCrFeMnNi та CrFe₂MnNi, що зміцнені попередньо синтезованими нанооксидами складу 80%Y₂O₃+20%ZrO₂ (mol.%). Середній розмір зерен у дисперсно-зміцнених сплавах близько 2 мкм. Оксидні виділення в сплавах характеризуються присутністю дрібних часток з середнім розміром близько 10 нм і щільністю ≈ 10²¹ м⁻³, а також незначної кількості більших часток з розмірами 50…150 нм. Встановлено якісний склад часток різного розміру. Досліджені механічні властивості сплавів при різних температурах. Показано, що міцнісні характеристики суттєво підвищуються при зміцненні сплавів нанооксидними частками. Методом механического легирования с последующим компактированием и спеканием получены высокоэнтропийные сплавы CoCrFeMnNi и CrFe₂MnNi, дисперсно-упрочненные предварительно синтезированными нанооксидами состава 80%Y₂O₃+20%ZrO₂ (mol.%). Средний размер зерен в дисперсно-упрочненных сплавах составил примерно 2 мкм. Оксидные выделения в сплавах характеризуются наличием мелких частиц со средним размером около 10 нм и плотностью ≈ 10²¹ м⁻³, а также незначительного количества больших частиц с размерами 50…150 нм. Установлен качественный состав частиц разного размера. Исследованы механические свойства сплавов при разных температурах. Показано, что прочностные характеристики значительно повышаются при упрочнении сплавов нанооксидными частицами.